Convergence and Stability of a Class of Iteratively Re-weighted Least Squares Algorithms for Sparse Signal Recovery in the Presence of Noise - Babadi, Behtash (IEEE Trans Signal Process, 2014)
In this paper, we study the theoretical properties of a class of iteratively re-weighted least squares (IRLS) algorithms for sparse signal recovery in the presence of noise. We demonstrate a one-to-one correspondence between this class of algorithms and a class of Expectation-Maximization (EM) algorithms for constrained maximum likelihood estimation under a Gaussian scale mixture (GSM) distribution. The IRLS algorithms we consider are parametrized by 0 < ν ≤ 1 and ε > 0. The EM formalism, as well as the connection to GSMs, allow us to establish that the IRLS(ν, ε) algorithms minimize ε-smooth versions of the ℓ(ν) ‘norms’. We leverage EM theory to show that, for each 0 < ν ≤ 1, the limit points of the sequence of IRLS(ν, ε) iterates are stationary point of the ε-smooth ℓ(ν) ‘norm’ minimization problem on the constraint set. Finally, we employ techniques from Compressive sampling (CS) theory to show that the class of IRLS(ν, ε) algorithms is stable for each 0 < ν ≤ 1, if the limit point of the iterates coincides the global minimizer. For the case ν = 1, we show that the algorithm converges exponentially fast to a neighborhood of the stationary point, and outline its generalization to super-exponential convergence for ν < 1. We demonstrate our claims via simulation experiments. The simplicity of IRLS, along with the theoretical guarantees provided in this contribution, make a compelling case for its adoption as a standard tool for sparse signal recovery.